PENGGUNAAN MEDIA GOOGLE EARTH PADA PEMBELAJARAN SKI DI SMP ISLAM MBAH BOLONG WATUGALUH DIWEK JOMBANG - Zailani Zailani; Jumari Jumari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
In the world of education, the development of information technology is starting to have a positive impact because with the development of information technology, the world of education is starting to show quite significant changes. With information and communication technology, we are able to process, transfer and move our scientific information effectively and efficiently and provide learning comfort between students and educators. So that the creation of a close relationship with students is able to produce a conducive Islamic religious education learning system in schools as desired.The aims of this research are (1) to describe the use of Google Earth media in Islamic Education learning at Mbah Bolong Islamic Junior High School, Watugaluh Diwek, Jombang, (2) to describe the supporting and inhibiting factors for using Google Earth media in SKI learning at Mbah Bolong Islamic Junior High School, Watugaluh, Diwek, Jombang.This research uses a qualitative approach with descriptive methods. Data collection was carried out using interviews, observation techniques and documentation. The informants in this research consisted of the Principal, Deputy Head of Curriculum, SKI Teacher who taught in class VII, students. Data collected for observations and interviews were analyzed using data source triangulation analysis techniques.The results of this research are 1) The use of Google Earth media in SKI learning at Mbah Bolong Islamic Junior High School, Watugaluh Diwek, Jombang is stated and refers to the Learning Module which adapts to the Achievement of Learning Objectives. 2) The supporting factors for using Google Earth media in SKI learning are adequate school facilities and the advantages of Google Eart and the inhibiting factors are that there must be an electricity network, an internet network must be available, an LCD projector must be available, a computer or laptop must be available. the results were very effective for several materials. Apart from that, it is to broaden students' insight into developments in information technology.